2004
DOI: 10.1264/jsme2.19.227
|View full text |Cite
|
Sign up to set email alerts
|

Lectin Variation in Members of <i>Rhizoctonia</i> Species

Abstract: Isolates from two multinucleate Rhizoctonia species, namely Rhizoctonia solani and Rhizoctonia circinata, and binucleate Rhizoctonia spp., were evaluated for the presence of lectins, using human erythrocytes. Isolates from R. solani had similar lectins across the anastomosis groups. Agglutination profiles, however, revealed individual preferences for human blood types but with a general preference for type A over B and O. R. solani lectins had a general affinity for N-acetyl-D-galactosamine and mucin. Also, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…These processes include cellular signaling, differentiation, and host-pathogen interactions through the specific recognition of glycol conjugates of the host cell membrane by lectins present on the surface of the fungal wall (Guillot and Konska 1997;Hamshou et al 2007;Khan and Khan 2011). In accordance with our study, fungal lectins have been previously detected in the mycelium and sclerotia of R. solani strains of different anastomosis groups (Kellens and Peumans 1991;Mghalu et al 2004) with a reported role in fungal growth and development (Leonidas et al 2007). Additionally, R. solani lectins were revealed to act as storage proteins (Skamnaki et al 2013).…”
Section: Carbohydrate-binding Genessupporting
confidence: 88%
“…These processes include cellular signaling, differentiation, and host-pathogen interactions through the specific recognition of glycol conjugates of the host cell membrane by lectins present on the surface of the fungal wall (Guillot and Konska 1997;Hamshou et al 2007;Khan and Khan 2011). In accordance with our study, fungal lectins have been previously detected in the mycelium and sclerotia of R. solani strains of different anastomosis groups (Kellens and Peumans 1991;Mghalu et al 2004) with a reported role in fungal growth and development (Leonidas et al 2007). Additionally, R. solani lectins were revealed to act as storage proteins (Skamnaki et al 2013).…”
Section: Carbohydrate-binding Genessupporting
confidence: 88%
“…A number of studies are devoted to the lectins of plant pathogenic basidiomycetes, such as Athelia rorfsii (teleomorph: Sclerotium rolfsii ) and various Rhizoctonia species [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. By the using of affinity chromatography, a lectin, RSA ( Rhizoctonia solani lectin), was isolated from Rhizoctonia solani mycelium [ 48 ].…”
Section: Intracellular Lectins From Mycelia Of Basidiomycetesmentioning
confidence: 99%
“…The protein is not glycosylated . The lectin was detected in R. solani strains of many different anastomosis groups . Furthermore, a detailed analysis of the accumulation and distribution of the RSA in the mycelium and the sclerotia revealed that the lectin is developmentally regulated .…”
Section: Introductionmentioning
confidence: 99%
“…Basidiomycetes constitute a rich source of fungal lectins exhibiting var-ious carbohydrate-binding properties and structures [2]. Although fungal lectins have a role as storage proteins [2,3] and are also involved in morphogenesis and development of the fungi, their physiological importance remains enigmatic [4][5][6]. In 1987, Vranken et al [7] first reported the purification and characterization of a lectin from Rhizoctonia solani (RSA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation